Changes in the avifauna in a high Andean cloud forest in Colombia over a 24‐year period (2017)
The upper altitude ecosystems of the Andes are among the most threatened by climate change. Computer models suggest that a large percentage of species in these ecosystems will be at risk of extinction and that avian communities will suffer disruption and impoverishment. Studies in other Andean countries lend some support to these predictions, but there are no quantitative data from Colombia appropriate to test these models. In 1991–1992, we conducted a bird survey in a high Andean cloud forest to gather information about the species present and their abundance. We attempted to replicate this earlier study 24 yr later to detect any changes in the avifauna and determine possible causes for those changes. From June 2015 to May 2016, we made bimonthly trips to the study site and identified all birds detected either visually or by voice along a number of trails. We supplemented our observational data by also capturing birds in mist-nets. Community species richness and composition as well as the overall abundance of birds changed little from 1991–1992 to 2015–2016, but nearly 30% of bird species changed in abundance. Changes in the presence or abundance of nine or 10 species reflected upward shifts in elevational limits potentially due to climate change. However, most changes in abundance appeared to reflect changes in the vegetation of the study area due to successional changes in forest and subparamo habitats and a large number of relatively recent treefalls of old canopy trees with heavy epiphyte loads and subsequent changes in the understory vegetation. Our results suggest that the effects of climate change on the avifauna in our study area at a high-altitude site in Colombia are apparently occurring more slowly than predicted by recent computer models, although we conclude that the possible effects of climate change should definitely be considered in future studies. However, single-site studies such as ours have limitations in documenting elevation shifts; the most conclusive and quantitative evidence for elevational shifts comes from long-term studies conducted over a wide range of elevations. As such, we recommend establishment of such a monitoring program in Colombia because data obtained from such a program might be important in designing measures to mitigate the effects of climate change and conserve biodiversity. © 2017 Association of Field Ornithologists